The Role Of Brand Image and Social Media Marketing On Wardah Skincare Product Purchasing Decisions - Doddy Adhimursandi; Rahmawati, Rahmawati; Gusti Noorlitaria Achmad (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to determine the influence of social media marketing and brand image on consumer decisions to buy Wardah brand skin care products. The population of this research is people who live in Balikpapan, Samarinda, and Bontang cities. The number of respondents is 109 who meet this research sample's criteria. This study uses structural equation modeling (SEM), which is measured using partial least squares (PLS). SmartPLS 3.0, a data processing software application tool, was used to conduct the analysis. The findings of this study indicate that brand image has an insignificant influence on customers' decisions to buy Wardah brand skin care products. This is because currently, there are many companies that are similar & offer the same benefits & functions and also because people trust customer evaluations and testimonials more than claims made unilaterally by a skin care product. Meanwhile, social media marketing significantly affects consumers' decisions to buy Wardah brand skin care products.